The exponentiated odd weibull-topp-leone-g family of distributions: model, properties and applications - Chamunorwa, Simbarashe; Oluyede, Broderick; Makubate, Boikanyo; Chipepa, Fastel (Botswana International University of Science & Technology, 2022)
In this paper, a new generalized family of distributions called the exponentiated odd Weibull-Topp-Leone-G (EOW-TL-G) family of distributions is presented. A linear representation of the proposed model is also presented. A simulation study to examine the consistency of the maximum likelihood estimates is conducted. Usefulness of the new proposed model was assessed by means of applications to two real data examples.